Groundwater quality assessment of Chilanchil Abay watershed: the case of Bahir-Dar City waste disposal site - Haile, Dargie; Gabbiye, Nigus (Journal of Environmental Engineering and Landscape Management, 2021)
Improper dump sites have served many years as an ultimate disposal site for all types of waste; municipal solid waste, industrial sewage and hazardous waste in developing countries such as Ethiopia. Physical, chemical and biological processes interact simultaneously to bring about the overall decomposition of the wastes (chemically laden leachate). If not, deal properly, such kind of dumping site can cause pollution to groundwater (because of Leachates) and surface water (through contaminant transportation by flooding and groundwater movements). Therefore, this study investigates the spatial and temporal variation of groundwater quality within the Chilanchil Abay watershed during dry and wet season due to the waste disposal site of the Bahir Dar city. Water samples were collected from 6 sampling points of groundwater from 30th March to 20th August by a monthly period. Over 10 water quality parameters such as pH, TDS, Electrical conductivity, Turbidity, Temperature, DO, BOD, COD, TC, NO3- and PO43–, were analyzed. Moreover, the overall status of the groundwater quality of the study area was evaluated by the Canadian Water Quality Index. Based on the result of this model the status of the groundwater sample points throughout the study area were raged from 42 to 46.2 (marginal status).